Open lower limb fractures in the UK trauma system: A multicentre prospective audit of current practice. Issue 6 (June 2021) - Claireaux, Henry A; Beaumont, Oliver; Griffin, Xavier L; ,; Parker, Simon JM; Howgate, Daniel J; Fennelly, Joseph T; Neal-Smith, Gregory; Wali, Anuj; Healicon, Richard EJ; Thind, Arron AT; Usman, Mehvish; et al.
Highlights: A prospective, multicentre, audit including 239 patients with open fractures from 3 Major Trauma Centres and 5 Trauma Units in the UK. 31.3% of patients from Major Trauma Centres were transferred in from another facility. 42.3% of patients with open fractures were managed at some point in a Trauma Unit. BOAST/BAPRAS Open Fracture standards are poorly adhered to across the study population. Trauma unit patients are excluded in many other studies and registries due to the model for data collection that privileges data collection in MTCs. Abstract: Introduction: Open fractures represent limb-threatening and life-changing injuries. Clear standards define how patients with these injuries should be managed in the UK. The study of open fractures is, therefore, a key measurable example of major trauma management as a whole. This study was conducted to characterise the demographic, assessment and treatment of patients sustaining lower limb open fractures across UK Regional Trauma Networks. Methods: A prospective, multicentre, audit was conducted according to a prespecified protocol against the relevant British Orthopaedic Association (BOA) & British Association of Plastic, Reconstructive & Aesthetic Surgeons (BAPRAS) standards for Trauma. All UK hospitals treating adults with open fractures were eligible to take part in the study. Patients included were injured during a six month collection period at each site. Results: 3 Major Trauma Centres (MTCs) and 5 Trauma Units (TUs) were enrolled, with data collected by 24 collaborators. 239 patients were included, 11 had bilateral open fractures. There were 38 patient datasets collected from TUs and 201 from MTCs. Patients were predominantly male with high energy injuries. 31.3% of patients from MTCs were transferred in from another facility. Antibiotics were given to 41.7% of patients within 1 hour. 74.4% of limbs with open fractures had a splint applied in the emergency department. 85.8% of patients had a documented orthoplastics plan. 41.7% of patients with a high energy injury had their wound debrided within 12 hours. Discussion: 42.3% of patients with open fractures in our cohort were managed at some point in a TU, indicating triage was required within the trauma network. Due to sampling, we may be under-estimating the number of patients passing through TUs, however, we have demonstrated that this cohort exists. These patients are under-represented in many other studies and registries such as the Trauma Audit Research Network (TARN) due to the funding model for data collection that privileges data collection in MTCs. Conclusion: This study gives extensive new insight into the demographics and management of patients with open lower limb fractures in the UK, demonstrating a widespread involvement of TUs and consistent deviation from national standards.